(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article discusses the concepts, objects and research methods of composite materials, the results obtained and research on improving the quality of manufactured materials. In addition, the properties of the reinforcing filler and the matrix from which they are made, their ratio and the orientation of the filler are selected. In composite materials, the location and arrangement of reinforcing elements that ensure resistance to external influences is of particular importance.